O gênero diário de leitura e o desenvolvimento de capacidades de linguagem - Galhardo, Carla Mascarenhas de Oliveira (2009)
The development of reading ability is essential to promote learning in different cultural contexts. The formative process of critical readers, able to understand and produce different texts that circulate socially, is the main function of the educational institution. Therefore, it is important that the school provides didactic resources to guide the teachers in the formative process of the readers, helping them to develop the necessary language abilities to comprehension and production of texts. The development of reading ability is essential to promote learning in different cultural contexts. The formative process of critical readers, able to understand and produce different texts that circulate socially, is the main function of the educational institution. Therefore, it is important that the school provides didactic resources to guide the teachers in the formative process of the readers, helping them to develop the necessary language abilities in students comprehension and production of these texts. Concerning with these needs, our research is focused on the issue of reading practice, with a systematic work of reading through a didactic sequence of reading diary genre. We believe that the command of this genre by the teachers can be a valuable didactic tool and the command of this genre by the students can help them to develop language abilities that are necessary to the production and to a more interactive reading. The theoretical and methodological framework of this research is the Sociodiscursive Interacionism ISD (Bronckart,1997/2003;2006, and others), which postulates that the human being interacts socially mediated by the language use that is discursively materialized in textual genres. The framework to work out at the didactic sequence is based on works developed by Dolz & Schneuwly (1998), and the reading diary is based on works of Machado (1998; 2002; 2005; 2007), specially on work developed by Machado,Lousada and Abreu-Tardelli (2007). The results show that the teaching with the didactic sequence of reading diary promotes in students the development of language abilities necessary for its production and enables the interactive reading practice. However, despite of positive results, we consider that the didactic sequence used in this research requires adjustments in some aspects, especially in a bigger development of certain language abilities